Regulations on Access to Financial Information to Improve Taxpayer Compliance with Law No. 9/2017 and its Implementation Rules - Tjhai, Fung Njit (Universitas Pelita Harapan, 2024)
The purpose of this research is to explore and analyze regulations for access to financial information for tax purposes to increase taxpayer compliance. The research approach in this study is qualitative normative based on literature and field studies in the form of collecting access data and following up on inbound and domestic AEOI based on access to information by tax administration. This study finds that for easy access to financial information for tax purposes both in the context of AEOI and the implementation of the tax laws, Law No. 9/2017 authorizes access to financial information to the Director General of Taxes (DGT) by setting aside the confidentiality of financial information in the Law of Tax Procedures and the Banking Law, access to banking financial information has positively increased tax compliance, but compulsory reporting of accounts with minimum balance of Rp1 billion have the potential to trigger rush of bank funds. On the other hand, it had reduced the effectiveness of Law No. 9/2017 to increase tax compliances for individuals who have accounts’ balance less than Rp1 billion at the end of the reporting calendar year. It can be suggested to amend the formulation of the provisions of Article 2 paragraph (3) of Law 9/2017 refers to the Common Reporting Standard (CRS) which must contain financial information, including NPWP with NIK (Resident Identification Number) for certainty and to eliminate doubts.